2017
DOI: 10.1002/glia.23199
|View full text |Cite
|
Sign up to set email alerts
|

Microglia may compensate for dopaminergic neuron loss in experimental Parkinsonism through selective elimination of glutamatergic synapses from the subthalamic nucleus

Abstract: Parkinson's disease (PD) symptoms do not become apparent until most dopaminergic neurons in the substantia nigra pars compacta (SNc) degenerate, suggesting that compensatory mechanisms play a role. Here, we investigated the compensatory involvement of activated microglia in the SN pars reticulata (SNr) and the globus pallidus (GP) in a 6-hydroxydopamine-induced rat hemiparkinsonism model. Activated microglia accumulated more markedly in the SNr than in the SNc in the model. The cells had enlarged somata and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 55 publications
5
49
0
Order By: Relevance
“…Therefore, we investigated the effects of NA on primary cultured microglial cells. As has been described previously (Aono et al, ), glutamate (Glu; 5 μM) enhanced phagocytic internalization of red fluorescent particles of PKH26 (Figure a). When simultaneously incubated with Glu (5 μM) and NA (10 μM) for 2 hr, the Glu‐mediated enhancement of phagocytosis was abolished.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, we investigated the effects of NA on primary cultured microglial cells. As has been described previously (Aono et al, ), glutamate (Glu; 5 μM) enhanced phagocytic internalization of red fluorescent particles of PKH26 (Figure a). When simultaneously incubated with Glu (5 μM) and NA (10 μM) for 2 hr, the Glu‐mediated enhancement of phagocytosis was abolished.…”
Section: Resultssupporting
confidence: 81%
“…Circadian changes in LC‐derived NA contents in the brain (Aston‐Jones & Bloom, ) and the suppressive effects of NA on microglia are well‐known (Ishii et al, ; Mori et al, ). Glu enhances phagocytic activity of primary cultured rat microglia (Aono et al, ), and NA overcomes the Glu‐induced enhancement, as was shown in the present study. Decline of NA contents caused by senescent degeneration of the LC has been implicated in pathologic activation of microglia in Alzheimer's disease (Heneka et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The microglia-derived proinflammatory cytokines and chemokines may also contribute to aggravation. Injection of 6-hydorxydopamine (6-OHDA) into the striatum or medial forebrain bundle is used to prepare the PD rat model [47,48] . In the model, DA neurons in the SNc primarily undergo degeneration, and microglia then become activated in response to damage-associated molecular patterns (DAMPs), such as high mobility group box-1 protein (HMGB1) released from damaged neurons [49] .…”
Section: Response Of Microglia In Brain Pathology In the Absence Of Bmentioning
confidence: 99%